Long‐term safety and efficacy of left atrial appendage closure in patients with small appendage orifices measured with transesophageal echocardiography. Issue 2 (15th November 2022) - Wang, Binhao; Wang, Zhao; Chu, Huimin; He, Bin; Fu, Guohua; Feng, Mingjun; Du, Xianfeng; Liu, Jing; Yu, Yibo
Abstract: Background: The Watchman device is the most widely used occluder but is indicated in atrial fibrillation (AF) patients with a maximal left atrial appendage (LAA) orifice diameter between 17 and 31 mm. We aimed to compare the long‐term safety and efficacy of left atrial appendage closure (LAAC) between patients with a small LAA (<17 mm) and those with an indicated LAA (17–31 mm) measured by transesophageal echocardiography (TEE). Methods: A total of 369 AF patients treated with LAAC between March 2015 and February 2019 were included and divided into two groups based on the maximal LAA orifice diameter measured by TEE: small LAA group ( n  = 22) and indicated LAA group ( n  = 347). Periprocedural complications and long‐term clinical outcomes were compared. Results: The Watchman device was successfully implanted in all patients. Mean device compression was higher in the small LAA group. Four patients (1.2%) in the indicated LAA group experienced pericardial effusion, and none experienced pericardial effusion in the small LAA group. Device‐related thrombus was detected in one (4.5%) patient in the small LAA group and five (1.4%) in the indicated LAA group ( p  = .310). After a mean follow‐up period of 4.1 ± 1.6 years, one patient in the small LAA group (4.5%; 1.1/100 person‐years) and four in the indicated LAA group (1.2%; 0.3/100 person‐years) suffered an ischemic stroke ( p  = .266). Conclusions: The safety and efficacy of LAAC with the Watchman device were comparable between patients with small and indicated LAA orifice diameters measured by TEE.